An Experimental Study for Performance and Emissions of a Small Four-Stroke SI Engine For Modern Motorcycle - Hamada, K. I.; M. M., Rahman (Universiti Malaysia Pahang, 2014)
The performance and emissions of a spark-ignited, port-injected, gasoline-fuelled, water-cooled, small-size modern motorcycle engine were investigated. For this purpose, an experimental test-rig was built up utilizing a small motorcycle engine for carrying out the practical tests. Experimental tests were performed for a range of engine speeds, various air-fuel ratios with a WOT condition and fixed timing of injection and ignition events. The experimental test-rig results consist of torque, power, brake mean effective pressure (bmep), AFR and emissions of the exhaust gas for various engine-dynamometer speeds. The accuracy of the test-rig measurement was verified by comparing both torque and brake power with benchmark data, which appear in the motorcycle technical manual. The acquired results indicated that conservation of the conventional mode of small engine characteristics is the distinctive impression for the tested engine. Further achievements are planned based on utilizing the developed test-rig and the attractive potential of a dual-fuel technique for reducing emissions and producing acceptable levels of torque and power.